1999
DOI: 10.1038/sj.cgt.7700066
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral recombinant GM-CSF-encoding virus as gene therapy in patients with cutaneous melanoma

Abstract: Seven immunocompetent, revaccinated patients with surgically incurable cutaneous melanoma underwent treatment of dermal and/or subcutaneous metastases with twice-weekly intratumoral injections of escalating doses (10 4 Ϫ2 ϫ 10 7 plaque-forming units (PFU)/lesion; 10 4 Ϫ8 ϫ 10 7 PFU/session) of a vaccinia/GM-CSF recombinant virus for 6 weeks. Patients with stable or responding disease were maintained on treatment until tumor resolution or progression. Systemic toxicity was infrequent, dose-related, and limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
241
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(248 citation statements)
references
References 19 publications
(16 reference statements)
7
241
0
Order By: Relevance
“…One way is to arm the virus with an immunostimulatory factor such as granulocyte-macrophage colony-stimulating factor. 29 Another method is to arm it with a gene-directed enzyme prodrug therapy (GDEPT). 7,30,31 Other investigators have shown that combined virus/prodrug treatment may enhance the replication/spread of oncolytic adenovirus in mouse tumor models.…”
Section: Introductionmentioning
confidence: 99%
“…One way is to arm the virus with an immunostimulatory factor such as granulocyte-macrophage colony-stimulating factor. 29 Another method is to arm it with a gene-directed enzyme prodrug therapy (GDEPT). 7,30,31 Other investigators have shown that combined virus/prodrug treatment may enhance the replication/spread of oncolytic adenovirus in mouse tumor models.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccinia oncolysate has been studied as a vaccine in early stage melanoma. [156][157][158][159][160][161][162][163][164][165] Results suggested a good tolerability and survival advantage compared with historical controls. However, an unpublished prospective controlled trial failed to validate the use of vaccinia oncolysate.…”
Section: Vacciniamentioning
confidence: 99%
“…Medium was removed and cells were fixed with 0.5 ml fixation solution (2% paraformaldehyde, 0.2% gluteraldehyde) for 5 min RT. Fixed cells were washed three times with PBS and stained with 0.5 ml coloring solution (0.1% X-gal in 5 mm K 3 Fe(CN) 6 , 5 mm K 4 Fe(CN) 6 , 2 mm MgCl 2 ) at 37°C.…”
Section: Titer Determination Of Recombinant Particle Batchesmentioning
confidence: 99%
“…Possibilities that are already explored in the clinic involve immunization with autologous tumor cells, genetically modified with recombinant viral vectors to produce interferon-gamma, IL-4, IL-12, and GM-CSF. [1][2][3][4][5][6] At present, GM-CSF appears to be the most efficient cytokine for obtaining optimal immune responses. 7 Within the context of the use of cytokine gene-modified autologous tumor cell vaccines, currently, in the clinic retrovirus vectors are applied most widely for delivery of the cytokine gene to the tumor cells, [7][8][9][10][11] although other viral delivery systems are also under investigation.…”
Section: Introductionmentioning
confidence: 99%